Technology Optimization for Equitable Access to Education and Health Services in Poverty Alleviation - Khairi, Muhammad (Metromedia, 2023)
Technology has become a key instrument for improving access to education and health services for the poor. Innovations in Information and Communication Technology (ICT) have opened up new opportunities to overcome geographical and economic barriers that have been major obstacles to obtaining essential services. Online learning platforms enable students from different economic backgrounds to access quality education without location restrictions. Telemedicine and digital health applications have made it easier for the poor to obtain medical services without having to face distance and transportation costs. The effectiveness of technology in poverty alleviation is highly dependent on the readiness of infrastructure, the level of digital literacy, and regulations that support the inclusiveness of technology access. The main challenges faced include limited internet networks in remote areas, digital literacy gaps, and high technology adoption costs for low-income communities. A comprehensive policy strategy is needed, including the development of digital infrastructure, improving technological literacy, and economic incentives for inclusive and sustainable technological innovation. Collaboration between the government, private sector, and non-governmental organizations is a key factor to ensure that technology can be implemented equitably. Optimal utilization of technology can contribute to poverty alleviation, improving quality of life, and achieving sustainable development goals.